(untitled) (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: To assess glucose levels in adults with diabetes at a Swiss tertiary hospital when transitioning from insulin delivery with a sensor-augmented pump with (predictive) low-glucose suspend ([P]LGS) to a hybrid-closed loop (HCL) and from a HCL to an advanced hybrid-closed loop (AHCL). METHODS: Continuous glucose monitoring data for 44 adults with type 1 diabetes transitioning from (P)LGS to hybrid-closed loop and from hybrid-closed loop to advanced hybrid-closed loop were analysed, including the percentage of time spent within, below, and above glucose ranges. In addition, a subgroup analysis (n = 14) of individuals undergoing both transitions was performed. RESULTS: The transition from a (P)LGS to a hybrid-closed loop was associated with increased time in range (6.6% [2.6%–12.7%], p <0.001) and decreased time above range (5.6% [2.3%–12.7%], p <0.001). The transition from a hybrid-closed loop to an advanced hybrid-closed loop was associated with increased time in range (1.6% [−0.5%–4.5%], p = 0.046) and decreased time above range (1.5% [–1.8%–5.6%], p = 0.050). Both transitions did not change the time below range. In the subgroup analysis ([P]LGS → HCL → AHCL), the time in range increased from 69.4% (50.3%–79.2%) to 76.5% (65.3%–81.3%) and 78.7% (69.7%–85.8%), respectively (p <0.001). CONCLUSIONS: Glucose levels significantly improved when transitioning from a (P)LGS to a hybrid-closed loop. Glucose levels improved further when switching from a hybrid-closed loop to an advanced hybrid-closed loop. However, the added benefit of an advanced hybrid-closed loop was comparably smaller. This pattern was also reflected in the subgroup analysis.